1988
DOI: 10.1007/bf00270903
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexectomy for the treatment of chronic infected hydrocephalus

Abstract: Choroid plexectomy was performed for chronic infected hydrocephalus in 17 children via a direct open approach. In 16 cases, the CSF was sterilized soon after the plexectomy. In 37% of cases, the hydrocephalus was arrested without a shunt. The incidence of seizures did not increase after plexectomy. Removal of the choroid plexus was controlled by scintigraphy. Neuropsychological results were not encouraging, probably related to the long history of chronic ventricular infection. Surgical mortality was 6%. Choroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…A small series of 17 patients with "chronic hydrocephalus" underwent primary choroid plexectomy; the authors reported a 37% success rate, defined as avoidance of CSF-diversion procedures. 81 Subsequent small series in selected patients who underwent either CPC or plexectomy found advantages in terms of reduced rates of reoperation, readmission, or operative complications. 92,144 The underlying motif for these reports points to adequate patient selection as a key determinant in maximizing the chances of shunt avoidance when performing isolated choroid plexus-disruption procedures.…”
Section: Modulation Of Csf Secretion By Surgical Intervention Of the mentioning
confidence: 99%
“…A small series of 17 patients with "chronic hydrocephalus" underwent primary choroid plexectomy; the authors reported a 37% success rate, defined as avoidance of CSF-diversion procedures. 81 Subsequent small series in selected patients who underwent either CPC or plexectomy found advantages in terms of reduced rates of reoperation, readmission, or operative complications. 92,144 The underlying motif for these reports points to adequate patient selection as a key determinant in maximizing the chances of shunt avoidance when performing isolated choroid plexus-disruption procedures.…”
Section: Modulation Of Csf Secretion By Surgical Intervention Of the mentioning
confidence: 99%
“…-Introduction), and according to the experimental results obtained that way, it seemed logical that the removal of the choroid plexuses (if the CSF pathways are blocked) should result in preventing the development of hydrocephalus, and in the recovery and healing of the patients as well. For many years, this surgical procedure was the most popular form of hydrocephalus treatment, but because of universally poor results, it has no place in the current treatment of hydrocephalus (Lapras et al, 1988;Milhorat, 1976; see Section 7.1. -Choroid plexectomy).…”
Section: Controversy Between Hydrocephalus and The Classical Hypothesismentioning
confidence: 99%
“…However, over the decades it became clear that bilateral extirpation and/or cauterization of the choroid plexuses invariably failed to benefit the patients. As was mentioned, because of universally unsatisfactory results, choroid plexectomy was abandoned by neurosurgeons as a treatment for hydrocephalus, so today it is an operation of historic interest only, and has no place in the treatment of hydrocephalus (Lapras et al, 1988;Milhorat, 1976). Despite these discouraging results, the introduction of the endoscopic method renewed an interest in different surgical procedures on the choroid plexuses, especially in the mid 90s (Enchev and Oi, 2008;Pople and Ettles 1995;Wellons et al, 2002).…”
Section: Choroid Plexectomymentioning
confidence: 99%
“…Scarff, however, continued to advocate choroid plexectomy and Dandy's later technique of third ventriculostomy as the simplest and most physiological methods of surgical treatment. This method of treatment (endoscopic coagulation) has been revived more recently for use in certain subgroups of hydrocephalic children [18][19][20].…”
Section: Hydrocephalus In Ancient Historymentioning
confidence: 99%